Influence of weather conditions and density of Doru luteipes (Dermaptera: Forficulidae) on Diatraea saccharalis (Lepidoptera: Crambidae) egg mortality - Fenoglio, Maria Silvina (2007)
The infuence of weather factors and the predator Doru luteipes Scudder density on Diatraea saccharalis (F.) egg predation was studied. Mortality of D. saccharalis eggs was determined by artiÞcially infesting maize plots with egg masses at various times within each of two maize-growing seasons. Each egg cohort was monitored every 24Ð48 h to determine the fate of eggs, and predation rates were calculated. Doru luteipes were sampled every 7Ð10 d, and the mean air temperature, the minimum percentage of relative humidity, and rainfall accumulations were recorded during the egg exposure period. To test the effects of abiotic and biotic variables on egg predation, we used a generalized linear model (GLM). Diatraea saccharalis egg predation was negatively associated with rainfall, whereas D. luteipes density and mean temperature were positively correlated with mortality. The implications of these Þndings for the management of D. saccharalis are discussed.